Predictor Factors of Difficult Laparoscopic Cholecystectomy in Cholelithiasis Patients in Dr. Mohammad Hoesin General Hospital Palembang - Hero Akbar; Hafizd Komar; Theodorus (Sriwijaya Journal of Surgery, 2020)
Background: Laparoscopic cholecystectomy is the gold standard for cholecystectomy and can be performed by trained general surgeons. However, the percentage of complications that occur from cholecystectomy laparotomy is approximately 20 percent. So, it is necessary to research risk factors for complications. Methods: This research is an analytic observational study with a cross-sectional design using preoperative data and intraoperative findings of laparoscopic cholecystectomy. Age, gender, body mass index, history of cholecystitis, number of stones, and location of stones are identified as predictors that affect the difficulty of laparoscopic cholecystectomy. The data collection was performed at the Mohammad Hoesin Hospital Palembang Department from July 2019- July 2020. Results: Of the 67 research samples, a Chi-square test was performed, and the factors that had a significant relationship were the body mass index (P-Value 0,000), history of cholecystitis (P-Value 0,000), number of stones (P-Value 0.049), and stone location. (P-Value 0.002). Conclusion: The backward stepwise logistic regression using the four variables showed that the history of cholecystitis had an independent effect (OR-adjusted 28.889 and P-Value 0.000).